DIGITAL LEADERSHIP: BUILDING ADAPTIVE ORGANIZATIONS IN THE DIGITAL AGE - Kawiana, I Gede Putu (Sean Institute, 2023)
The digital era has changed the business and organizational landscape significantly, triggering rapid changes in technology, work culture and market dynamics. In facing the challenges and opportunities presented by the digital era, adaptive leadership is critical in ensuring the survival and success of the organization. Leaders who have the ability to lead and utilize technology are called digital leaders. This study aims to analyze the role of digital leadership in building adaptive organizations in the context of the digital era. This research will use a qualitative approach with descriptive methods. The results show that digital leadership is not only about understanding technology, but also about formulating a vision that integrates technology into business strategy, builds a culture of innovation, develops employees' digital skills, focuses on customers, and creates organizational flexibility. Digital leaders need to have the ability to adapt quickly to change, design responsive organizational structures, and maintain data security and privacy. By applying these digital leadership principles, organizations can optimize the potential of technology, achieve sustainable business goals, and adapt successfully to the relentless changes of the digital transformation era.